Analisis Resepsi Sastra pada Cerpen Karena “Kita Tidak Kenal” Karya Farida Susanty - Frastika, Anggi; Hayuning Tyas, Pinasti; Anggita Harahap, Zihan Manja; Adelia Fahreza, Shinta (Mimbar Kampus: Jurnal Pendidikan dan Agama Islam, 2024)
This research aims to determine the acceptance of readers, namely students of Indonesian Language and Literature Education, Muhammadiyah University of North Sumatra, towards the intrinsic elements in the short story Because We Don't Know Farida Susanty's work and its implications for literature learning in Indonesian Language and Literature Education. The research method used is a qualitative descriptive research method. The data collection techniques used are reading techniques and note-taking techniques obtained from research questionnaires, namely questionnaires. The data used in this research is readers' reception of the short story Because We Don't Know Farida Susanty's work. The results of this research are readers' reception of the short story "Because We Don't Know" by Farida Susanty and its implications for literature learning in the Indonesian Language and Literature Education Study Program. Based on data analysis, the results obtained include reader acceptance of the intrinsic elements of the short story Because We Don't Know Farida Susanty's work, which was produced after respondents answered 5 questions on the questionnaire, regarding the implications of reader acceptance of short stories in literature learning.